Tetronic(®)-based Composite Hydrogel scaffolds seeded with Rat-Bladder Smooth Muscle Cells for Urinary Bladder Tissue Engineering Applications - Sivaraman, Srikanth (J Biomater Sci Polym Ed, 2014)
Natural hydrogels such as collagen offer desirable properties for tissue engineering, including cell adhesion sites, but their low mechanical strength is not suitable for bladder-tissue regeneration. In contrast, synthetic hydrogels such as PEG allow tuning of mechanical properties, but do not elicit protein adsorption or cell adhesion. For this reason, we explored the use of composite hydrogel blends composed of Tetronic (BASF) 1107-acrylate (T1107A) in combination with extracellular matrix (ECM) moieties collagen and hyaluronic acid seeded with bladder smooth muscle cells (BSMC). This composite hydrogel supported BSMC growth and distribution throughout the construct. When compared to the control (acellular) hydrogels, mechanical properties (peak stress, peak strain, and elastic modulus) of the cellular hydrogels were significantly greater. When compared to the 7-day time point after BSMC seeding, results of mechanical testing at the 14-day time point indicated a significant increase in both ultimate tensile stress (4.1 kPa to 11.6 kPa) and elastic modulus (11.8 kPa to 42.7 kPa) in cellular hydrogels. The time-dependent improvement in stiffness and strength of the cellular constructs can be attributed to the continuous collagen deposition and reconstruction by BSMC seeded in the matrix. The composite hydrogel provided a biocompatible scaffold for BSMC to thrive and strengthen the matrix; furthering this trend could lead to strengthening the construct to match the mechanical properties of the bladder.